Housing and Urbanization in Africa : Unleashing a Formal Market Process - Collier, Paul; Venables, Anthony J. (World Bank, Washington, DC, 2014)
The accumulation of decent housing matters both because of the difference it makes to living standards and because of its centrality to economic development. The consequences for living standards are far-reaching. In addition to directly conferring utility, decent housing improves health and enables children to do homework. It frees up women's time and enables them to participate in the labor market. More subtly, a home and its environs affect identity and self-respect. Commentary on the emergence of an African middle class has become common, but it is being defined in terms of discretionary spending and potential for consumer markets. A politically more salient definition of a middle class will be in terms of home ownership and the consequent stake in economic stability. This paper examines why such a process has not happened in Africa. Our hypothesis is that the peculiarity of housing exposes it to multiple points of vulnerability not found together either in private consumer goods or in other capital goods. Each point of vulnerability can be addressed by appropriate government policies, but addressing only one or two of them has little payoff if the others remain unresolved. Further, the vulnerabilities faced by housing are the responsibility of distinct branches of government, with little natural collaboration. Unblocking multiple impediments to housing therefore requires coordination that can come only from the head of government: ministries of housing have neither the political weight nor the analytic capacity to play this role effectively. Yet in Africa, housing has never received such high political priority. This in turn is because the centrality of housing in well-being and of housing investment in development has not been sufficiently appreciated.